The Confessions Rule and the Charter - Stewart, Hamish (McGill Law Journal / Revue de droit de McGill, 2009)
AbstractThe confessions rule—the requirement that the Crown prove the voluntariness of the accused’s statements to persons in authority—is a well-established rule of criminal evidence and is closely connected with the constitutional principle against self-incrimination that it structures. The confessions rule is thus a natural candidate for recognition as a principle of fundamental justice under section 7 of the Canadian Charter of Rights and Freedoms. However, there are two distinct routes by which the confessions rule might be constitutionalized. Under the “rule of evidence” approach, the confessions rule would be recognized as an aspect of the accused’s constitutional right to a fair trial. Under the “rights violation” approach, the conduct of the state in obtaining an involuntary statement would be treated as a violation of the accused’s constitutional rights.In R. v. Singh, despite having previously adopted the “rule of evidence” approach, the Supreme Court of Canada applied the “rights violation” approach and linked the confessions rule very closely to the constitutional right to silence. In so doing, the Court conflated the distinct protections offered by the right to silence on the one hand and the confessions rule on the other, particularly when Singh is read in light of other recent cases that appear to weaken the confessions rule. Fortunately, the Court’s recent decisions concerning the confessions rule may also be read as instances of appellate deference to trial judges’ factual findings on voir dires. Thus, they leave room for the recognition that neither the right to silence nor the confessions rule is reducible to the other, and that each has a distinct role to play: the right to silence protects the accused’s decision to speak at all, while the confessions rule concerns the accused’s motivations for speaking as he or she did.